The Long-Run Trend of Residential Investment in China - Ding, Ding (IMF Working Papers; Working Paper, 2018)
In this paper we analyze the fundamental drivers of China's residential investment as a share of its GDP. Our analysis indicates that the economic structural changes that led to rebalancing toward consumption were the key driver of the rising residential investment to GDP ratio in China. We project that residential investment would moderate from the current level of 9 percent of GDP to around 6 percent by 2024, and its contribution to real GDP growth would decline gradually from currently about half percent of GDP to slightly negative over this period, barring policy intervention. The decline in the growth contribution of residential investment reflects the projected somewhat slower pace of rebalancing going forward and the envisaged increases in labor costs due to demographic changes.